A Literature Review on Evolving Earnings Management Techniques - Kaur, Raghuveer; Khanna, Ashu (Prabandhan: Indian Journal of Management, 2016)
Earnings management is a wide area of concern. The critical nature of the subject has garnered significant focus of academicians and practitioners. Over the years, several research articles have comprehensively examined the state of earnings management, various models used, and the scope of the study. These studies have focused on the understanding of earnings management, various models employed in the detection and prediction of earnings management, and the future areas of the study. The present paper is a summary of the recent research studies conducted in the area of earnings management techniques between the years 2009-2015. The paper reviewed the existing research articles that discussed new methods and existing methods on detecting earnings management that added a new perspective in detecting earnings management. The research studies employed several new techniques and models along with the use of variables, which can be used to gain significant information on indicating the presence of earnings management. The use of accounting ratios, neural network, and cash flow from operations are some of the examples that the researchers have used, giving altogether a new approach towards diagnosing earnings management.